Judicial independence without public trust? Reassessing institutional legitimacy in Sierra Leone's democratic governance - Thomas Sheku Marah (JURNAL ILMU SOSIAL, 2026)
This study examines the relationship between judicial independence, public trust, and institutional legitimacy in Sierra Leone's democratic governance framework. Using a qualitative case study approach, the research analyzes constitutional provisions, governance reports, institutional assessments, and relevant scholarly literature to evaluate whether formal judicial independence is sufficient to generate institutional legitimacy. The findings indicate that judicial independence alone does not automatically translate into public confidence or institutional authority. While judicial reforms have strengthened constitutional safeguards and institutional autonomy, legitimacy remains contingent upon citizens' perceptions of judicial effectiveness, fairness, accessibility, and accountability. The study demonstrates that public trust functions as a critical mechanism linking judicial independence to democratic governance outcomes. Consequently, institutional legitimacy emerges not solely from legal protections but from the interaction between judicial autonomy and societal confidence. The article argues for a governance-centered understanding of judicial independence that incorporates public trust as a fundamental dimension of institutional legitimacy.